2021
DOI: 10.1021/acs.jpclett.1c00425
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Proton Transfer Thermodynamics in SARS-CoV-2 Main Protease: Implications for Catalysis and Inhibitor Design

Abstract: The catalytic reaction in SARS-CoV-2 main protease is activated by a proton transfer (PT) from Cys145 to His41. The same PT is likely also required for the covalent binding of some inhibitors. Here we use a multiscale computational approach to investigate the PT thermodynamics in the apo enzyme and in complex with two potent inhibitors, N3 and the α-ketoamide 13b . We show that with the inhibitors the free energy cost to reach the charge-separated state of the active-site dyad is lower, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…MD simulations were carried out for the Chymotrypsin-like catalytic domain I + II [ 22 , 41 ] of the two isoforms using, in turn, the Amber99sb-ildn [ 42 ] and the OPLS-AA/M FFs [ 32 ] with the GROMACS code [ 43 ] (version 2018.8). In the H–C isoform, H41 was assigned to the tautomer with the protonated N δ [ 25 ]. The potential parametrization for the PF-07321332 ligand was generated using two web interfaces: PrimadORAC [ 44 ] for AMBER FF and LigParGen [ 45 ] for OPLS-AA FF.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…MD simulations were carried out for the Chymotrypsin-like catalytic domain I + II [ 22 , 41 ] of the two isoforms using, in turn, the Amber99sb-ildn [ 42 ] and the OPLS-AA/M FFs [ 32 ] with the GROMACS code [ 43 ] (version 2018.8). In the H–C isoform, H41 was assigned to the tautomer with the protonated N δ [ 25 ]. The potential parametrization for the PF-07321332 ligand was generated using two web interfaces: PrimadORAC [ 44 ] for AMBER FF and LigParGen [ 45 ] for OPLS-AA FF.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, a thorough MD study on the dimer [ 24 ] showed that the ion-pair configuration of the dyad is not compatible with a catalytically competent binding mode for peptide substrates. Substrate docking on the 3CL pro with the dyad in neutral form is hence supposed to favor the CYS to HIS PT [ 25 ] preceding the acylation step in the catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations